Clinicopathological profiling of chronic kidney disease in cats presented at University Veterinary Hospital, Universiti Putra Malaysia from 2016-2021 - Wong, Jun Yong; Abdullah, Rasedee; Othman, Azalea Hani (Universiti Putra Malaysia, 2026)
Chronic kidney disease (CKD) is common in cats, typically showing increased prevalence in geriatric patients. This study profiled clinicopathological changes across CKD stages in 136 cats-without concurrent diseases-selected from the Veterinary Laboratory Services Unit database. Cases were classified into stages II, III, and IV based on the International Renal Interest Society (IRIS) creatinine guidelines. Signalment and clinicopathological data including hematology, serum biochemistry and urinalysis were analysed. Domestic Shorthair (77.2%) was the most common breed affected, followed by Persian (5.9%) and mixed breed cats (5.9%). Males (60.1%) were more frequently diagnosed than females (37.5%). Notably, cats aged 5 to 8 years (n=48) were overrepresented with CKD regardless of stage. Erythrocyte counts and haemoglobin levels were significantly higher (p<0.05) in stage II than in stage IV. Similarly, packed cell volume, reticulocyte counts, and urine specific gravity were significantly higher (p<0.05) in stage II than in stages III and IV. Levels of band and segmented neutrophils, as well as monocytes increased as stages advance, reaching the highest in stage IV cats (p<0.05). Phosphate level was significantly higher (p<0.05) in stages IV than in stages II and III. Urea and creatinine concentrations in stage IV were approximately four times higher than those in stage II. High-normal sodium and albumin, low-normal chloride and normal potassium were common across all stages. These findings suggest that non-regenerative anaemia and tubular dysfunction characterise later CKD stages. Understanding these patterns is vital for monitoring disease progression and optimising therapeutic interventions.